2018
DOI: 10.1111/sms.13021
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry during Functional Movement Screening and injury risk in junior football players: A replication study

Abstract: An indicator of movement quality and potential injury risk during Functional Movement Screen (FMS) testing is the presence of asymmetry when comparing the left and right sides of the body. The aim of the study was to investigate the reproducibility of the injury risk model proposed in our previous research (Chalmers et al. 2017; derivation study) that showed an increased injury risk for elite junior Australian football players demonstrating ≥2 asymmetrical FMS subtests. We used a direct replication design. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…Second, pre‐season physical fitness tests were of limited value in predicting new injuries in two prospective studies on male elite youth football players (n = 84 and n = 67) . Finally, in a prospective study on 382 male elite junior Australian rules football players, an association between physical fitness compounds (lower aerobic endurance, greater sprint, and agility performances) with increased injury risk was first demonstrated, but not reproduced …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, pre‐season physical fitness tests were of limited value in predicting new injuries in two prospective studies on male elite youth football players (n = 84 and n = 67) . Finally, in a prospective study on 382 male elite junior Australian rules football players, an association between physical fitness compounds (lower aerobic endurance, greater sprint, and agility performances) with increased injury risk was first demonstrated, but not reproduced …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies related to various elements of physical fitness have attempted to identify factors that contribute to injury and illness risk in young athletes, although not at the elite level. Typically, physical fitness tests encompass components such as cardiorespiratory endurance, muscular strength, flexibility tests, and functional movement tests . Prior research studies on the adult population have demonstrated an association between higher levels of aerobic fitness and decreased injury risk, whereas research on the relationship between physical fitness level and illness risk is limited and mostly focus on increasing training loads .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies on FMS and sports injury in soccer players, Chalmers et al (2018) investigate the relationship between FMS asymmetry and number of games played before first injury and reported to be closely associated with a significant increase in prospective injury risk ( Grygorowicz et al, 2013 ; Miller and Susa, 2019 ; Sprague et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%